A robust methodology for prediction of trust and reputation values - Hussain, Farookh Khadeer; Chang, Elizabeth; Hussain, Omar (Association for Computing Machinery (ACM), 2008)
In this paper, we present the FC direct trust value-based decision making methodology, for making direct trust value based decisions regarding interactions in (a) a given context and during the current time slot, and (b) a given context and at a future time slot. The direct trust value-based decision making methodology models the context specific nature of trust and the dynamic nature of trust to make direct trust value-based decisions regarding interactions. Additionally in this paper, we present the FC reputation-based trust decision making methodology, for making reputation-based trust decisions regard ing interactions, if direct trust value-based decisions cannot be made. The FC reputationbased trust decision making methodology can make reputationbased trust decisions regarding interactions in (a) a given context and during the current time slot, and (b) a given context and at a future time slot.